If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -3 = p + -5 Reorder the terms: -3 + 2p = p + -5 Reorder the terms: -3 + 2p = -5 + p Solving -3 + 2p = -5 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -3 + 2p + -1p = -5 + p + -1p Combine like terms: 2p + -1p = 1p -3 + 1p = -5 + p + -1p Combine like terms: p + -1p = 0 -3 + 1p = -5 + 0 -3 + 1p = -5 Add '3' to each side of the equation. -3 + 3 + 1p = -5 + 3 Combine like terms: -3 + 3 = 0 0 + 1p = -5 + 3 1p = -5 + 3 Combine like terms: -5 + 3 = -2 1p = -2 Divide each side by '1'. p = -2 Simplifying p = -2
| 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 | | X^2+100+60-3x+30-4x=180 | | -6+[25+(-12)]=31 | | -13+2x=-52+13 | | -6+[25+(-12)]=7 | | -6+[25+(-12)]=19 | | 4=5+2x | | 5x+17-4x=-2-10 | | X/Y=7/11 | | 3x^2-(3m-2)x-(3m+1)=0 | | 1/3*1/3*1/3*1/3*a*a*b*b*c | | 5x-3y=106 | | 16+7yi=8x+i | | x-6=3(2x) | | f-5-3f=7 | | 2x+(x+1)=2 | | 2(4w+9)/4=-10 | | 5x/6-3/2=x/3 | | 0.5(7y+1)-3=8 | | 5(f-1)=25 | | 15m+2n-6m+8n= | | 15x^2+42x=9 | | (1/7)y-4=-18 | | 66=x/-2 | | 9-x=3-5x | | 0=276x^2+2x-0.25 | | -5/2x=-5 | | (1/3)y-4=-7 | | 27/.. |